Masjid Sebagai Pusat Pendidikan Agama Islam - Rifai, Muhammad (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
One of the places to pray for the Muslims is a mosque although in fact, in Islamic law the whole earth can be used to perform prayer, except in places where there is a prohibition to perform prayer in it.as the word of the Messenger of Allaah 'alaihi Wasallam which means: "It has been made for me this earth a place of prostration and in a holy state." (H.R. Abu Dawud). This type of research is field research, with a skin descriptive approach. The results of this study showed that the mosque not only serves as a place to pray, but there are other functions, among others, as social, economic, educational, political, arts and cultural development. The author wants to explain the function of the mosque as exemplified by the Prophet Muhammad shallallaahu ‘alayhi Wasallam so that the existing mosques can become centers of educational activities as when the Prophet Muhammad shallallaahu‘ alayhi wasallam first.